Mortality and reoperations following treatment of acetabular fractures in patients ≥ 70 years: a retrospective cohort study of 247 patients - Johan Ljungdahl; Björn Hernefalk; Anna Pallin; Anders Brüggemann; Nils P Hailer; Olof Wolf (Acta Orthopaedica)
Background and purpose: Evidence for long-term outcomes following acetabular fractures in older adults is limited. We aimed to evaluate mortality, complications, and need for subsequent surgical procedures in operatively and nonoperatively treated older patients with acetabular fractures. Methods: Patients aged ≥ 70 years with acetabular fractures treated at Uppsala University Hospital between 2010 and 2020 were included. Fractures were classified according to Letournel. Local medical records were analyzed and cross-referenced with the Swedish Arthroplasty Register to identify reoperations and delayed arthroplasty procedures. Follow-up time ranged from 2–12 years. Primary outcome was mortality 1 year after injury. Descriptive statistics, survival analysis using the Kaplan–Meier method, and logistic regression models were used. Results: 247 patients (67% men) with a median age of 80 years (range 70–102) were included. Most patients were ASA class 3 (67%). 148 (60%) patients were treated operatively. The 1-year mortality was 15% (95% confidence interval [CI] 9–21) in the operatively and 29% (CI 19–37) in the nonoperatively treated group. Difference in adjusted mortality rates between treatments did not reach statistical significance. 20% of patients treated with open reduction internal fixation (ORIF) underwent some form of reoperation. In the nonoperatively treated group, 1% had a delayed THA. Conclusion: The 1-year mortality following acetabular fractures in older people was 21% (CI 15–26), underscoring the frailty of this patient group. ORIF alone was associated with a 20% reoperation rate while the rate of delayed surgical treatment in patients selected for nonoperative treatment was 1%.